An Indigenous Academic Perspective to Preserving and Promoting Indigenous Knowledge and Traditions: A Fiji Case Study - Ali, Wahab (The Australian Journal of Indigenous Education, 2016)
Indigenous knowledge is multidimensional encompassing the beliefs, practices, arts, spirituality and other forms of traditional and cultural experiences that belong to Indigenous communities globally. In order to protect, preserve and recognize the knowledge of the Indigenous people of Fiji, known as the iTaukei, the University of Fiji has established a Centre for iTaukei Studies. The Centre apart from its cultural dimension has adopted the western system of disseminating knowledge through publications, text books and teacher education programmes. While maintaining the importance of preserving the originality of the Indigenous cultural identity and practices, the paper highlights how the infusion of the cultures of the Indigenous people and that of the Indo-Fijians, who have co-existed together for over 100 years, has shaped the unique multicultural landscape in Fiji.